IBU CERDAS AI:Pemberdayaan Kelompok Perempuan melalui Literasi Artificial Intelligence untuk Pendidikan Anak, Produktivitas Keluarga, dan Keamanan Digital - Desy Sary Ayunda; Wulanda; Novi Sari Liani; Nur Elisyah; Asmaul Husna (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2026)
The rapid development of Artificial Intelligence (AI) offers significant opportunities for communities to enhance family education, household productivity, and digital security. However, women's understanding of AI utilization remains limited, particularly in using technology in a practical, safe, and responsible manner. This community service program aimed to improve AI literacy among mothers through the use of ChatGPT as the primary tool to support children's education, family productivity, and digital security awareness. The program involved 30 mothers and was implemented through socialization sessions, training, hands-on practice, mentoring, and evaluation using pretests and posttests. The results indicated a substantial improvement in participants’ AI literacy, with average scores increasing from 40.0% in the pretest to 86.4% in the posttest, representing an improvement of 46.4 percentage points. Furthermore, 83% of participants were able to create prompts to support their children's learning, 70% successfully generated promotional ideas for family businesses, and 88% demonstrated an understanding of basic digital security principles after the training. Participant satisfaction with the program reached an average of 93.8%. These findings suggest that the Ibu Cerdas AI (Smart Mothers AI) program was effective in enhancing women's capacity to utilize AI productively, educationally, and safely within the family environment.